COMPETITIVE STRATEGIES IN A PRIVATE KINDERGARTEN : A CASE STUDY OF A RAUDHATUL ATHFAL IN MALANG - Ine Madinatul Munawaroh (Tadbir: Jurnal Manajemen Pendidikan Islam, 2026)
Kindergartens located in less strategic areas often face significant challenges in attracting a sufficient number of students. This study aims to analyze the competitive advantage strategies implemented by a foundation in managing a kindergarten facing such challenges, particularly concerning its location and suboptimal student enrollment. The research focuses on identifying superior development strategies to enhance the school’s competitiveness and sustainability, including program differentiation, service quality improvement, innovative marketing approaches, and strengthening relationships with the local community. A qualitative case study method was employed at a Raudhatul Athfal (RA) school under a foundation in Malang, Indonesia. Data were collected through observation, in-depth interviews, and documentation. The findings indicate that effective competitive strategies include personal approaches to parents, value-based flagship programs, the use of social media for branding, and flexible tuition policies. Value-based differentiation strategies have proven to enhance the community's positive perception, gradually contributing to increased student enrollment. This study provides practical insights for school administrators and foundations in designing relevant strategies despite limited resources. Keywords : competitive advantage, kindergarten, foundation strategy, differentiation, case study